Seasonal and daily activity of free-ranging European bison females fitted with GPS collars (European Bison Conservation Newsletter, 2012)
We studied activity of European bison females in free-ranging groups in the European part of Russia. Animals fitted with GPS-collars were observed from March until July. The whole patterns of diurnal activity (the highest during the evening twilight and the lowest in the dawn) were the same between the snowy and snowless period while European bison were more active during the latter (Apr-Jul). There were no periods of the sharp increase in activity during the day but there is a period of the more prominent decrease in activity in the evening. There was also a period of the sharper decrease in the morning in May which could be related to pregnancy and calving.
Keywords: European bison; telemetry; daily activity; seasonal activity; collars; free-ranging group